"We Wouldn't Change Him for the World, but We'd Change the World for Him": Parents, Disability, and the Cultivation of a Positive Imaginary - Thomas, Gareth M. (Current Anthropology, 2024)
Down's syndrome (DS) occupies a curious position in the public imaginary in the United Kingdom. There is a growing public, and positive, presence of people with DS in cultural outlets and across networks of people with experiences of disability. Simultane
Keywords: Cultivation; Down's Syndrome (DS); Parents; Positive Imaginary; Disability